The Use of Genre Based Approach to Improve Students Writing’s Skill in Recount Text - Indah, Nuria; Rini, Setia (UNDIKMA, 2024)
This study aims to enhance students' writing abilities in recount texts at the SD School of Life Lebah Putih's fourth grade. This study employs a quasi-experimental design to investigate the effectiveness of the genre-based approach in improving students' writing skills in recount text. Data obtained pre-test and post-test. it can be inferred from the research findings and discussion that the pupils' mean score growth between the pre- and post-test served as evidence. The pre-test mean score for the students was 66.84, which was categorized as fairly good, whereas the post-test mean score was higher at 79.36, which was categorized as excellent. Additionally, the data analysis revealed that the t-test value was greater than the value in the t-test table (11.050>1,711). It implies that the difference was substantial. H1 was approved whereas H0 was disapproved. In other words, the employment of a genre-based approach (GBA) can help students write recount texts more effectively.